Water quality criteria for an acidifying ocean: Challenges and opportunities for improvement. (June 2016) - Weisberg, Stephen B.; Bednaršek, Nina; Feely, Richard A.; Chan, Francis; Boehm, Alexandria B.; Sutula, Martha; Ruesink, Jennifer L.; Hales, Burke; Largier, John L.; Newton, Jan A.
Abstract: Acidification has sparked discussion about whether regulatory agencies should place coastal waters on the Clean Water Act 303(d) impaired water bodies list. Here we describe scientific challenges in assessing impairment with existing data, exploring use of both pH and biological criteria. Application of pH criteria is challenging because present coastal pH levels fall within the allowable criteria range, but the existing criteria allow for pH levels that are known to cause extensive biological damage. Moreover, some states express their water quality criteria as change from natural conditions, but the spatio-temporal distribution and quality of existing coastal pH data are insufficient to define natural condition. Biological criteria require that waters be of sufficient quality to support resident biological communities and are relevant because a number of biological communities have declined over the last several decades. However, the scientific challenge is differentiating those declines from natural population cycles and positively associating them with acidification-related water quality stress. We present two case studies, one for pteropods and one for oysters, which illustrate the opportunities, challenges and uncertainties associated with implementing biological criteria. The biggest challenge associated with these biological assessments is lack of co-location between long-term biological and chemical monitoring, which inhibits the ability to connect biological response with an acidification stressor. Developing new, ecologically relevant water quality criteria for acidification and augmenting coastal water monitoring at spatio-temporal scales appropriate to those criteria would enhance opportunities for effective use of water quality regulations. Highlights: 303(d) assessments for ocean acidification are challenging. Chemical assessment is limited by pH criteria at levels below that known to cause biological damage. Biological assessments are limited by lack of co-location between biological and chemical monitoring. Changes to existing criteria are needed to protect aquatic life and support acidification management.